2016
DOI: 10.1177/1046496416645409
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Task Interdependence and Functional Leadership in Schools

Abstract: The context of the research was senior leadership teams in schools in Australia. The study investigated relationships between task interdependence, psychological collectivism, self-efficacy for teamwork, and team member perceptions of leadership functions. A cross-sectional and correlational research design was employed. Fifty-seven senior leadership teams composed of principals and senior teachers within two Catholic education systems in New South Wales, Australia, participated in the study. Data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…Task interdependence may affect personal collective efficacy in terms of influencing the levels of collective cognition activities in teams, which relate to personal collective efficacy. In addition to the importance of task interdependence in team processes as an objective phenomenon, it has also been suggested that team members' perceptions of task interdependence may also influence team processes (Barnett & McCormick, 2016). In addition, team members' perceptions of task interdependence may vary over time, because of the way they work interdependently may change (Gully, et al, 2002).…”
Section: Research Arguments and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Task interdependence may affect personal collective efficacy in terms of influencing the levels of collective cognition activities in teams, which relate to personal collective efficacy. In addition to the importance of task interdependence in team processes as an objective phenomenon, it has also been suggested that team members' perceptions of task interdependence may also influence team processes (Barnett & McCormick, 2016). In addition, team members' perceptions of task interdependence may vary over time, because of the way they work interdependently may change (Gully, et al, 2002).…”
Section: Research Arguments and Hypothesesmentioning
confidence: 99%
“…Perceived collective cognition activities will positively be related to personal collective efficacy. As mentioned earlier, task interdependence may be operationalized objectively and subjectively (Barnett & McCormick, 2016). That is, even when the objective task interdependence is identified at the beginning of teamwork, team members' perceptions of task interdependence may change over time dynamically (Gully et al, 2002).…”
Section: Research Arguments and Hypothesesmentioning
confidence: 99%
“…Our study answers the call for more research on the potential limitations of leader humility in certain organizational contexts (Ou et al, 2018; Tangney, 2009). In addition, most previous studies using the SIT have argued that a leader’s proactive participation, such as allocation of resources, has a stronger influence on team activities when members need to rely on each other (e.g., Barnett and McCormick, 2016; Hambrick et al, 2015; Liden et al, 2006). Our study extends such understanding by indicating that leader characteristics are important, but the influence of such characteristics varies in different team interaction contexts.…”
Section: Introductionmentioning
confidence: 99%